Study of the chemical composition of the thick extract of snapdragon herb - Ilyna, Sofia; Zhuravel, Iryna (Annals of Mechnikov’s Institute, 2024)
One of the current directions in the development of modern pharmacy is the search for new sources of biologically active compounds and the expansion of the range of phytopharmaceuticals. In this context, the Snapdragon (Antirrhinum majus L.), a herbaceous plant from the Plantaginaceae family, stands out as a promising object of research due to its potential for yielding biologically active compounds with valuable pharmacological properties. The plant’s chemical composition includes a significant number of bioactive compounds: amino acids, sugars, flavonoids, such as anthocyanidins, aurones, chalcones, and terpenoid compounds (iridoids, carotenoids). Due to the presence of these substances, the plant exhibits anti-inflammatory, wound-healing, antimicrobial, and antioxidant properties, which have been empirically confirmed. To expand the assortment of phytoremedies, we obtained a thick extract from the grass of this plant. The aim of this study was to examine the chemical composition of the Snapdragon herb extract, obtained from raw materials grown in Ukraine. Materials and methods: the object of study was the Snapdragon herb extract, obtained from a mixture of raw materials of the "Uvertura" and "Snappy" cultivars. Extraction was carried out using 70 % ethanol for 180 minutes by the maceration method. The plant material to solvent ratio was 1:10, and the raw material was ground into pieces measuring 5.0-8.0 mm. The chemical composition of the extract was analyzed using high-performance liquid chromatography (HPLC). The study was performed on a Milichrom A-02 liquid chromatograph with a ProntoSil-120-5-C18 AQ column, which was 75 mm long and 4 mm in diameter, with a stationary phase particle size of 5 µm. Two eluents were used in the experiment: A – 4 M lithium perchlorate solution, 0.1 M perchloric acid solution; and B – acetonitrile. The detectors were set to wavelengths of 210, 220, 230, 240, 250, 260, 280, and 300 nm. The thermostat temperature was set to 40 °C, and the flow rate of the mobile phase was 100 µL/min. The gradient of eluent B changed from 5 % to 100 % over 40 minutes. The initial sample volume was 800 µL, which was later increased to 4000 µL and 4300 µL. Chromatographic profiles were analyzed using the AlphaChrom software. Results: thirteen chemical compounds were identified using HPLC: flavonoids (luteolin-7-glucuronide, apigenin-7,4’-diglucuronide, quercetin-3-arabinofuranoside, quercetin-3-galactoside, quercetin-3-rhamnoside, kaempferol-3-glucoside, cyanidin), phenolcarbon chlorogenic acid, monosaccharide glucose, amino acids (phenylalanine, tryptophan), iridoid antirrhinoside and terpene myrcene. The obtained experimental data will be used for the standardization of the Snapdragon herb extract